Strategies for Accelerating MSME Financing Distribution at Bank Aceh in Compliance with Aceh Qanun No. 11 of 2018 - Irvan Murizal; Andri Soemitra; Nur Ahmadi bi Rahmani (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
After the issuance of Qanun Aceh Number 11 of 2018 concerning the Development of MSMEs (Article 60‎ paragraph 4), the Islamic financial system in Aceh Province has undergone a transformation, including Bank‎ Aceh, whose target for MSME distribution has reached 40%, but distribution is still 14.53%, so‎ the purpose of this article is to find out the strategic model for accelerating MSME financing‎ of Bank Aceh Syariah in achieving Qanun 11 of 2018. This research methodology‎ uses a qualitative approach to experts with Intepretative Structural‎ Modeling (ISM). The results show that the right strategy to accelerate‎ MSME financing in achieving Qanun No. 11 can be realized with ISM analysis‎ there are several conditions that need to be strengthened to support Bank Aceh's goals in‎ accelerating MSME financing in accordance with Qanun No. 11 of 2018. The results‎ explore strategies to accelerate the distribution of MSME financing at Bank Aceh in‎ order to fulfill Aceh Qanun No. 11 of 2018. This research analyzes four‎ key elements: needs, constraints, institutions involved, and effectiveness. From the‎ needs element, the main focus is on improving financing accessibility which includes‎ providing clear information and training for MSME actors. The constraints element‎ identifies the issue of unbankable MSMEs, i.e. business actors who do not meet‎ the requirements to obtain financing due to lack of documentation or collateral. ‎‎In terms of institutions involved, local governments play an important role in creating an enabling environment for MSMEs through policies and development programs. ‎‎Finally, effectiveness is measured through the increase in the number of MSMEs that successfully obtain financing and its impact on economic growth in Aceh. ‎